Tailoring intervention procedures to routine primary health care practice; an ethnographic process evaluation - Bruijnzeels Marc; Foets Marleen; de Bont Antoinette; Jansen Yvonne JFM; Bal Roland (BMC, 2007)
Abstract Background Tailor-made approaches enable the uptake of interventions as they are seen as a way to overcome the incompatibility of general interventions with local knowledge about the organisation of routine medical practice and the relationship between the patients and the professionals in practice. Our case is the Quattro project which is a prevention programme for cardiovascular diseases in high-risk patients in primary health care centres in deprived neighbourhoods. This programme was implemented as a pragmatic trial and foresaw the importance of local knowledge in primary health care and internal, or locally made, guidelines. The aim of this paper is to show how this prevention programme, which could be tailored to routine care, was implemented in primary care. Methods An ethnographic design was used for this study. We observed and interviewed the researchers and the practice nurses. All the research documents, observations and transcribed interviews were analysed thematically. Results Our ethnographic process evaluation showed that the opportunity of tailoring intervention procedures to routine care in a pragmatic trial setting did not result in a well-organised and well-implemented prevention programme. In fact, the lack of standard protocols hindered the implementation of the intervention. Although it was not the purpose of this trial, a guideline was developed. Despite the fact that the developed guideline functioned as a tool, it did not result in the intervention being organised accordingly. However, the guideline did make tailoring the intervention possible. It provided the professionals with the key or the instructions needed to achieve organisational change and transform the existing interprofessional relations. Conclusion As tailor-made approaches are developed to enable the uptake of interventions in routine practice, they are facilitated by the brokering of tools such as guidelines. In our study, guidelines facilitated organisational change and enabled the transformation of existing interprofessional relations, and thus made tailoring possible. The attractive flexibility of pragmatic trial design in taking account of local practice variations may often be overestimated.